Association between vitamin D levels and lower-extremity deep vein thrombosis: a case-control study - Korkmaz, Ufuk Turan Kursat (2021)
BACKGROUND: Vitamin D has relationships with pathogenesis and inflammation pathways in many diseases. Its deficiency may make clinicians think not only of supplementation but also of presence of other diseases. OBJECTIVE: To investigate the relationship between vitamin D levels and deep vein thrombosis (DVT), given that reduced levels are related to increased risk of cardiovascular diseases. DESIGN AND SETTING: Case-control study conducted in the cardiovascular surgery and family medicine departments of a hospital in Turkey. METHODS: A total of 280 participants were included: 140 each in the DVT and control groups. Basic clinical characteristics, comorbidities and serum 25-hydroxyvitamin D (25(OH)D) levels were recorded and then compared between the groups. Serum 25(OH)D levels were also evaluated separately in three subgroups (sufficient, insufficient and deficient). RESULTS: Serum 25(OH)D levels were significantly lower in the DVT group than in the controls (P < 0.001). Females in the DVT group had lower 25(OH)D levels than those in the control group (P = 0.002). Nonetheless, the median 25(OH)D level (16.41 ng/ml) of the control group was still below the reference value. Logistic regression analysis showed that 25(OH)D was a significant predictor of DVT. Weight, height and body mass index, which all presented interaction, were significant in the logistic regression analysis but not in individual analyses. CONCLUSION: The serum vitamin D levels of DVT patients were lower than those of controls. If the results obtained from our study are supported by further large-scale randomized controlled trials, vitamin D replacement may be brought into the agenda for protection against DVT.